Development of Solar Panel Monitoring System On Automatic Meter Reading - Tika Iswardhani; Astrie Kusuma Dewi; Chalidia Nurin Hamdani (Jurnal Polimesin, 2024)
In dealing with era society 5.0, a gas company uses the Automatic Meter Reading (AMR) system, which is a remote data reading automation technology system for measuring instrument data in the field, which then conveys the information to the center via communication media data. In the Metering/Regulating Station (M/RS) installation, AMR is connected to the Electronic Volume Converter (EVC) which functions to transmit data from measuring instrument readings in the EVC to the data collection server. The modem on the AMR system uses a power supply from the solar panel system during the day and a battery system at night. The system for handling incomplete data disturbances is currently still in corrective action due to the unavailability of a solar panel monitoring system in the AMR system, causing difficulties for the team in conducting root cause analysis due to problems with battery voltage which are unable to cure AMR. To change the operation and maintenance activities of the AMR system, which was previously corrective action into preventive action, the authors will design and build a long-distance integrated solar panel monitoring system at AMR with the following features monitoring temperature, voltage, and current modules of solar panels, monitoring temperature and battery loading, and AMR remote restart function.